Systematic Functional Analysis of Sigma (σ) Factors in the Phytopathogen Xanthomonas campestris Reveals Novel Roles in the Regulation of Virulence and Viability - Yang, Li-Yan; Yang, Li-Chao; Gan, Yong-Liang; Wang, Lin; Zhao, Wan-Zong; He, Yong-Qiang; Jiang, Wei; Jiang, Bo-Le; Tang, Ji-Liang (Frontiers in Microbiology, 2018)
The black rot pathogen Xanthomonas campestris pv. campestris (Xcc) is a model organism for the study of plant bacterial pathogenesis mechanisms. In bacteria, σ factors serve as important regulatory elements that respond to various environmental signals and cues. Though Xcc encodes fifteen putative σ factors little is known about their roles. As an approach to identify the potential role of each σ factor, we constructed mutations in each of the σ-factor genes as well as generating mutants deficient in multiple σ factors to assess these regulators potential additive functions. The work identified two σ70 factors essential for growth. Furthermore, the work discovered a third σ70 factor, RpoE1, important for virulence. Further studies revealed that RpoE1 positively regulates the expression of the hrp gene cluster that encodes the type III secretion system (T3SS) which determines the pathogenicity and hypersensitive response of Xcc on plants. In vivo and in vitro studies demonstrated that RpoE1 could bind to the promoter region and promote transcription of hrpX, a gene encoding a key regulator of the hrp genes. Overall, this systematic analysis reveals important roles in Xcc survival and virulence for previously uncharacterized σ70 factors that may become important targets for disease control.